KARAKTERISTIK BROWNIES PANGGANG DENGAN PENAMBAHAN KONSENTRASI IKAN GELODOK (Periophthalmodon schlosseri) YANG BERBEDA - Surya, Fauziah Nur; Surilayani, Dini; Pratama, Ginanjar; Haryati, Sakinah; Munandar, Aris; Aditia, Rifki Prayoga; Meata, Bhatara Ayi; Hasanah, Afifah Nurazizatul; Nuryadin, Devi Faustine Elvin (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2024)
Giant mudskipper is one of the fishery commodities that has good nutritionalcontent but has not been optimally utilized. One way to optimize itsutilization is by fortifying giant mudskippers in brownie products. Theobjective of this study was to determine the best brownies with the additionof giant mudskipper. The research method used a completely randomizeddesign (CRD) with 4 levels of giant mudskipper addition treatment in bakedbrownies, namely A (control), B (2%), C (4%), and D (6%). The tests carriedout included proximate analysis, hedonic analysis, and RecommendedDietary Allowance (RDA). The results of the analysis showed that treatmentD was the best with a high protein content of 10.21% and a low carbohydratecontent of 57.39%. The results of the hedonic analysis in all treatments foraroma, taste, and texture characteristics were statistically the same. Based onthe RDA test per sample of brownies as much as 20 g can meet the nutritionalneeds of women aged 19-29 years, protein 3.53-4.32%, carbohydrates 4.054.44%, and fat 9.87-11.22%. Meanwhile, for men aged 19-29 years protein 3.26-3.99%, carbohydrates 3.39-3.71%, and fat 8.55-9.73%.